Inhibition and minimum killing power of ajwa date extract (Phoenix dactylifera L.) against the growth of Streptococcus mutans : Uji daya hambat dan bunuh minimum ekstrak kurma ajwa (Phoenix dactylifera L.) terhadap pertumbuhan Streptococcus mutans - Amiruddin, Maqhfirah; Utama, Mohammad Dharma; Biba, Andi Tenri; Ramadhan, Sahrul (Makassar Dental Journal, 2025)
Streptococcus mutans is one of the constituent micro-organisms of dental plaque. These bacteria adhere to the denture base causing plaque that causes denture stomatitis. To reduce the growth of S.mutans, cleaning is done by brushing and soaking with herbal ingredients that can inhibit the growth of these bacteria, namely ajwa dates (Phoenix dactylifera L.). This study dis-cusses the inhibition and minimum killing power of ADE on the growth of S.mutans through experimental tests with disc diffu-sion and dilussion techniques with post test group type using 24 samples. The results of the Anova test obtained p-value= 0.000 (p<0.05), meaning that there is a significant difference between ADE treatments of 1.5625%, 3.125%, 6.25%, 12.5%, 25% and 50%. It is concluded that the MIC value of EKA is 12.5% while the MKC value of EKA is 50%.